Empowering or Directive Leadership, Job Satisfaction, and Disengagement in Urban-Regional Work Contexts of Indonesia - Husni, M. Fahrul; Gunawan, Hendra; Putri, Siti Aisyah (Jurnal Aplikasi Manajemen, 2025)
Employee disengagement has risen to prominence in Indonesia, where the realization of working across big cities and rural areas causes stress on both managers and employees. Disengagement undermines retention and has a negative impact on productivity at a time when our national economy is changing rapidly, so this topic is worth the time and attention it deserves. The present study investigates the impact of job satisfaction, directive leadership, and empowering leadership on disengagement among employees. It also evaluates whether workload modifies the magnitude of the relationship between disengagement and satisfaction in urban and regional workplaces. Using a quantitative design, the study collected survey data from 500 employees who were purposefully chosen to work in a variety of industries in both major cities and rural areas. The period of data collection in 2024 was May through August. Partial Least Squares structural equation modelling was employed in the analysis to investigate the correlations between the variables. The findings indicate that while directive leadership tends to increase disengagement, empowering leadership significantly reduces it. One important protective factor that lowers disengagement is job satisfaction.  Only empowering leadership shows a clear and consistent correlation with reduced disengagement, even though both directive and empowering leadership increase satisfaction. The analysis also reveals that workload moderates the influence of job satisfaction. There are diminishing returns to having happier employees when they’re overworked, and this dynamic is stronger in urban, compared with rural regional settings. Furthermore, incorporating workload as a moderating variable in an urban and regional setting of the study in a developing economy is a contribution. This shows that in order for job satisfaction to further enhance employee engagement, the role clarity, empowerment, and workload should be encouraged by the organization, with emphasis on the heavy demand of employees' energy use in large cities.